Antibodies to a Conserved Influenza Head Interface Epitope Protect by an IgG Subtype-Dependent Mechanism - Watanabe, Akiko; McCarthy, Kevin R.; Kuraoka, Masayuki; Schmidt, Aaron G.; Adachi, Yu; Onodera, Taishi; Tonouchi, Keisuke; Caradonna, Timothy M.; Bajic, Goran; Song, Shengli; McGee, Charles E.; Sempowski, Gregory D.; et al. (Cell, 2019)
Vaccines to generate durable humoral immunity against antigenically evolving pathogens such as the influenza virus must elicit antibodies that recognize conserved epitopes. Analysis of single memory B cells from immunized human donors has led us to characterize a previously unrecognized epitope of influenza hemagglutinin (HA) that is immunogenic in humans and conserved among influenza subtypes. Structures show that an unrelated antibody from a participant in an experimental infection protocol recognized the epitope as well. IgGs specific for this antigenic determinant do not block viral infection in vitro, but passive administration to mice affords robust IgG subtype-dependent protection against influenza infection. The epitope, occluded in the pre-fusion form of HA, is at the contact surface between HA head domains; reversible molecular “breathing” of the HA trimer can expose the interface to antibody and B cells. Antigens that present this broadly immunogenic HA epitope may be good candidates for inclusion in “universal” flu vaccines. [Display omitted] •Human B cells specific for a novel epitope on influenza A groups 1 and 2•Crystallography locates the epitope at the interface of the hemagglutinin head domains•Robust protection by antibodies to this epitope, dependent on IgG subclass•Protective, cross-group antibodies are encoded by diverse sets of Ig gene segments Antibodies targeting a novel site at the interface of the head domains of hemagglutinin provide broad, IgG-subclass-dependent protection against influenza.